2012
DOI: 10.1007/s11011-012-9290-1
|View full text |Cite
|
Sign up to set email alerts
|

The conundrum of iron in multiple sclerosis – time for an individualised approach

Abstract: Although the involvement of immune mechanisms in multiple sclerosis (MS) is undisputed, some argue that there is insufficient evidence to support the hypothesis that MS is an autoimmune disease, and that the difference between immune- and autoimmune disease mechanisms has yet to be clearly delineated. Uncertainties surrounding MS disease pathogenesis and the modest efficacy of currently used disease modifying treatments (DMTs) in the prevention of disability, warrant the need to explore other possibilities. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 137 publications
2
35
0
Order By: Relevance
“…Thus, it is possible that the exacerbated demyelination we observed in Hx 2/2 mice with EAE was due not only to massive Th17 cell infiltration, but also to the impairment of Hx-deficient oligodendrocytes to respond to exogenous insults. This conclusion is consistent with data showing that iron deposition in the brain contributes to MS pathogenesis (38). Thus, Hx would control, on one hand, systemic signals driving Th17 differentiation and, on the other hand, local signals in CNS affecting oligodendrocyte function.…”
Section: The Journal Of Immunology 5455supporting
confidence: 91%
“…Thus, it is possible that the exacerbated demyelination we observed in Hx 2/2 mice with EAE was due not only to massive Th17 cell infiltration, but also to the impairment of Hx-deficient oligodendrocytes to respond to exogenous insults. This conclusion is consistent with data showing that iron deposition in the brain contributes to MS pathogenesis (38). Thus, Hx would control, on one hand, systemic signals driving Th17 differentiation and, on the other hand, local signals in CNS affecting oligodendrocyte function.…”
Section: The Journal Of Immunology 5455supporting
confidence: 91%
“…Finally, a subgroup of adult and pediatric patients showing MS signs that appear to be provoked by iron deficiency has been identified. The symptoms are usually alleviated by iron supplementation (446). This can not only be easily explained by the high amount of iron needed for normal ODC development and function (159), but also substantiates the fact that iron excess is not responsible for MS initiation.…”
Section: B Circulatory Abnormalities In Pre-ms Brainmentioning
confidence: 81%
“…Increased iron levels (attributable to age pathology) have been connected to the disruption of the brain iron homeostasis leading to neurodegeneration, including MS [ 9 , 202 ]. MS patients have further been shown to exhibit increased levels of soluble transferrin (main iron transporter protein in the brain [ 204 , 205 ]) receptor associated with reinforced iron turnover [ 10 , 205 , 210 ]. Another study has reported an increased level of ferritin in the cerebrospinal fluid and serum of SPMS patients [ 211 ], providing the possible reason for extra iron delivery, since the H-ferritin receptor in neurons and oligodendrocytes is transferrin [ 205 , 212 ].…”
Section: Parametric T 2 -Relaxation Mappingmentioning
confidence: 99%
“…However, its diagnosis and treatment strategies are complicated by the presence of disease heterogeneity with distinct courses and diverse therapy responses. Patients are diagnosed as having early MS (formerly clinicaly isolated syndrome suspected of being MS (CIS)), clinicaly definite multiple sclerosis (CDMS), relapsing-remitting multiple sclerosis (RRMS), progressive-relapsing MS (PRMS), and primary- and secondary-progressive multiple sclerosis (PPMS, SPMS) [ 2 , 4 , 10 ]. Moreover, the disease causes variable degrees of motor, sensory, behavioral, mental, emotional, and cognitive impairment [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation